MICROHABITAT USE BY MERRIAM'S TURKEY BROODS IN WESTCENTRAL IDAHO - Frank B. Edelmann; Kerry P. Reese; Pete Zager (Wildlife Society Bulletin)
Abstract: We hypothesized that foraging and security requirements narrowly define suitable brood habitat for Merriam's turkey (Meleagris gallopavo merriami). We sampled microhabitat characteristics at 33 Merriam's turkey brood and paired dependent sites in westcentral Idaho during 1992 and 1993. Broods used microhabitat associated with invertebrate presence (73%), abundant ground cover (x¯ = 92 ± 1.1%, range = 77‐100%) consisting primarily of herbaceous vegetation (x¯ = 54%), and moderate visual obstruction (x¯ = 22 ± 1.8 cm [8.6 ± 0.7 in], range = 7–51 [3–20]). All but 1 brood site contained canopy cover (x¯ = 28 ± 3.2%, range = 0–73) by overstory trees (x¯ = 461 ± 102 trees/ha [187 ± 41 trees/ac], range = 0–2,025 [0‐820]), which we incidentally observed poults using for escape cover. Microhabitats with abundant ground cover by moderately dense herbaceous vegetation and sparse overstory canopy cover apparently provided suitable foraging and security conditions for Merriam's turkey broods.